Bacteria-related Events and the Immunological Response of Onset and Relapse Adult Crohn's Disease Patients. (22nd September 2018) - Cantó, Elisabet; Zamora, Carlos; Garcia-Planella, Esther; Gordillo, Jordi; Ortiz, M Angels; Perea, Lidia; Vidal, Silvia
Abstract: Background and Aims: Crohn's disease [CD] is a chronic, systemic inflammatory disease characterised by periods of remission and flare-ups. It has been associated with a disturbed gastrointestinal barrier function, an increase in the transport of luminal contents into the tissue, and lower immune tolerance. Methods: Peripheral blood samples were collected from healthy controls and 33 adult active flare-up CD patients. We classified patients as onset or relapse flare-up subjects, according to the days of disease evolution. Plasma levels of lipopolysaccharide-binding protein [LBP], fatty acid-binding proteins [FABP], and antibodies against bacterial lysates, interferons [IFN] and interleukin-6 [IL6] were measured by enzyme-linked immunosorbent assay [ELISA] in each group of patients. Results: Onset CD patients had higher plasma levels of LBP [57.32 ± 38.86 vs 30.22 ± 9.80 µg/ml] and IFNα [1.25 ± 0.23 vs 0.95 ± 0.36 log10 pg/ml] and lower levels of immunoglobulins G and A [IgG and IgA] antibodies against bacterial lysates than relapse CD patients. We also observed a subgroup of onset patients with the highest levels of LBP. In this subgroup, LBP correlated negatively with C-reactive protein [CRP]. Onset and relapse CD patients had similar levels of FABP6 and FABP2, though LBP and FABP6 correlated positively only in relapse patients. In relapse patients, anti- E coli IgG antibodies correlated positively with systemic IL6 and IFNα levels. Conclusions: Our findings suggest that onset and relapse flare-ups in adult CD patients are related to different systemic immune-related bacterial events. Characterising these differences may provide insights into the aetiology of Crohn's disease, and would help in the selection of appropriate therapies.